Taxing Family Size and Subsidising Child-specific Commodities? Optimal Fiscal Treatment of Households with Endogenous Fertility - Alessandro Cigno; Anna Pettini (Center for Economic Studies and ifo Institute (CESifo), 1999)
The effects and optimal choice of policy instruments affecting the family (child benefits, taxes on child-specific commodities, etc.) are examined within the context of a household economics model with fertility choice. The simultaneous consideration of child benefits and commodity taxes in the presence of endogenous fertility yields some remarkable results. One is that, if the government can distinguish between child-specific and adult-specific commodities, it may then be optimal to tax family size and subsidize child-specific commodities. Under more restrictive conditions, it is also shown that the tax system should be so designed, that children are a net tax liability if households are differentiated for the husband's income, a net tax asset if households are differentiated for the wife's wage rate.
Keywords: 330; Endogenous fertility; optimal indirect taxation; child-specific commodities; child benefits